Biodegradation and phenol tolerance by recycled cells of candida tropicalis NCIM 3556 - Varma, R. J.; Gaikwad, B. G. (International Biodeterioration & Biodegradation, 2009)
Resting cells of Candida tropicalis NCIM 3556 rapidly degraded almost completely 2 g L(-1) phenol in 16h. In this study, we explored the possibility of further increasing the efficiency of the culture by repeatedly reusing the cell for biodegradation. The effect of continuous recycling of whole cells of C. tropicalis, for biodegradation of phenol indicated that though with each recycle of the cell there was steady decline in phenol biodegradation the conversion was appreciable for five recycle (similar to 70%) and reached half-life of 50% after eleven recycles. Inhibition due to substrate, recycling of cells and adaptation of residual cell were estimated and an equation derived; which indicated that the cell resilience to phenol increased with each cycle and at the end of eleven recycle adaptation was 68%. However, when the adapted cells were sub cultured and showed marginal increase <10% in biodegradation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Candida tropicalis; Inhibition; phenol; Recycle; Tolerance

Biodegradation of phenol by the yeast candida tropicalis: an investigation by NMR spectroscopy - Phalgune, U. D.; Rajamohanan, P. R.; Gaikwad, B. G.; Varma, R. J.; George, S. (Applied Biochemistry and Biotechnology, 2013)
The process of phenol biodegradation by the yeast Candida tropicalis NCIM 3556 in aqueous medium was studied by H-1, C-13, and DOSY NMR techniques. Samples at regular intervals were centrifuged to separate the cells, and H-1 spectral data were collected at 400 MHz. Though a gradual decrease in the concentration of phenol was observed, after an incubation period of similar to 8 h, formation of any intermediate products could not be detected. Experiments carried out with uniformly C-13-labeled phenol also failed to detect formation of any carboxylic acid intermediates during degradation. The studies indicated that the phenol was completely degraded to carbon dioxide and water in approximately 20 h. Self-diffusion coefficient measurements showed that the lifetime of phenol in the bound form is too small to impart any change in its diffusion behavior and the intermediates formed are converted to carbon dioxide and water at a very fast rate.
Keywords: biocatalysis; Carboxylic acid; Diffusion; Enzyme; NMR spectroscopy; phenol